EVALUASI FORMULARIUM RUMAH SAKIT KELAS C DI DAERAH ISTIMEWA YOGYAKARTA (EVALUATION OF TYPE C HOSPITAL FORMULARIES IN SPECIAL PROVINCE YOGYAKARTA) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Background: As many pharmaceutical products on the market today are copy drugs, prototype drugs and non-essential drugs. Those products often offer no therapeutic advantage over other product that is already available. Therefore, appropriate selec¬tion was needed to support rational use of drugs. Drug selection through hospital formulary is one way to increase efficiency of drug management. The objective of this study was to evaluate and compare profile of 7 hospital formulary in Yogyakarta, to learn about the process of developing and revising the formulary and to learn the criteria for drug selection. Methods: The study was designed as a non-experimental, descriptive-analytical, ex¬plorative case study. It was conducted in 5 public and 2 private hospital type C around Yogyakarta. The quantitative data was obtained from hospital formulary, shipment facture and stock report. Chi-square test was applied for the statistical analysis. The qualitative data included in-depth interviews with DTC (Drug and Therapeutic Committee) member and representative doctors of ward. The qualitative data was ana¬lyzed by a content analysis method, findings were identified and codified, and then they were grouped according to their content. Qualitative findings were presented as text. Results: The result showed that the number of brand name products in public hospi¬tal less than private hospital (296-532 vs 513-1575). Indicators which more in public hospital than private hospital were the percentage of essential drugs (41-71% vs 20¬28%), the percentage of availability of generic drug (26-50% vs 17-18%), the per¬centage of drugs with generic name (26-48% vs 17-18%) and the percentage of drugs with primary literature (73-90% vs 67-73%) and the percentage drugs with single component (41-71% vs 20-28%). Statistic analysis of each indicators public vs private hospital were significant (P= 0,00).Those indicators show that in public hospi¬tal better than private hospital. The percentage of non-formulary drugs procurement and non-formulary drugs that available in stock was influenced by frequency of revision of hospital formulary and drug policy, which related to addition and deletion process the formulary. Non-formu¬lary drugs procurement was low in hospital, which revised their formulary frequently, but hospitals which do not have policy to addition and deletion will be increase non-formulary drugs procurement. Criteria for drug selection, which generally use in hos¬pital, were price (based on discounted price), quality (certificate of good manufactur¬ing product), and lag time of delivery and continuity of delivery. The physician atten¬dance in the process of developing and maintaining formulary was not satisfied. Regular meeting to manage the formulary was not established. Both in public and private hospital, DTC tend to accommodate the doctors' request on drug. Conclusions: It was concluded that the quality of formulary in public and private hospital type C in Yogyakarta was not satisfied. The process for developing and revising hospital formulary was not well established. Keywords: hospital formulary, evaluation, development process, revising process, and criteria for drug selection